2008
DOI: 10.1517/14728220802564390
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and the vasculature: can we teach an old drug new tricks?

Abstract: Background : Vitamin D is a steroid hormone known for its role in regulating levels of calcium and phosphorus. Vitamin D has important autocrine/paracrine roles and it is involved in vascular biology. Clinical studies have shown a relationship between vitamin D levels and cardiovascular health, and low levels of vitamin D metabolites have been associated with higher incidence of congestive heart failure and increases in mortality. Objective : To summarise the effect of vitamin D on cardiovascular pathology, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 102 publications
0
11
0
Order By: Relevance
“…These results add to the growing body of evidence implicating VitD deficiency in adverse cardiovascular outcomes in humans (Kristal-Boneh et al 1997;Krause et al 1998;Valdivielso et al 2009) and the ability of VitD to ameliorate the high blood pressure in SHR rats (Borges et al 1999) and increase flow-mediated vasodilation, an indicator of endothelial vasodilator function, in adult humans (Harris et al 2011;Jablonski et al 2011). Blood pressure was elevated by 11 (males) and 20 mmHg (females) in our study, similar to the 20 mmHg reported previously for VitD deplete male rats (Weishaar & Simpson, 1987) and VitD receptor knockout mice (Li et al 2002).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…These results add to the growing body of evidence implicating VitD deficiency in adverse cardiovascular outcomes in humans (Kristal-Boneh et al 1997;Krause et al 1998;Valdivielso et al 2009) and the ability of VitD to ameliorate the high blood pressure in SHR rats (Borges et al 1999) and increase flow-mediated vasodilation, an indicator of endothelial vasodilator function, in adult humans (Harris et al 2011;Jablonski et al 2011). Blood pressure was elevated by 11 (males) and 20 mmHg (females) in our study, similar to the 20 mmHg reported previously for VitD deplete male rats (Weishaar & Simpson, 1987) and VitD receptor knockout mice (Li et al 2002).…”
Section: Discussionmentioning
confidence: 54%
“…osteomalacia and rickets), it is becoming increasingly evident that VitD has myriad effects on physiological function due, in large part, to the presence of VitD receptors in most tissues. VitD deficiency has been linked with autoimmune (Ponsonby et al 2002), neurological (McGrath, 2001; Eyles et al 2003), and cardiovascular diseases (Zittermann, 2006; Nemerovski et al 2009; Valdivielso et al 2009). There is an apparent inverse relationship between cardiovascular disease and UV exposure in adult humans (Rostand, 1997; Krause et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, high phosphate levels and low 25OH vitamin D levels were also predictors of atheromatosis progression. Indeed, a potential role for phosphate and 25OH vitamin D levels has been previously suggested in the progression of atherosclerosis (33)(34)(35)(36)(37). Furthermore, a significant interaction between phosphate levels and age was found, showing that, when phosphate levels are .3.6 mg/dl, the association with age is much stronger.…”
Section: Discussionmentioning
confidence: 77%
“…Patients with CKD, even at early stages, demonstrate higher risk for the development of cardiovascular disease (1,2), enhancing morbidity and mortality in this population (3). A variety of traditional cardiovascular risk factors such as hypertension, diabetes, dyslipidemia (2), and nontraditional variables such as endothelial cell dysfunction (4), inflammation (2), low vitamin D levels (5,6), or hyperphosphatemia (7)(8)(9) begin to act very early in the course of CKD, accelerating the pathogenesis of cardiovascular disease. Taking into account that traditional and CKD-specific risk prediction equations explain only a portion of the cardiovascular disease associated with CKD, the search for new risk factors for cardiovascular disease in patients with CKD continues.…”
Section: Introductionmentioning
confidence: 99%